2013
DOI: 10.1186/1475-2875-12-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cytokines, chemokines and cellular immune responses in pre-school Nigerian children infected with Plasmodium falciparum

Abstract: BackgroundMalaria is a major cause of morbidity and mortality worldwide with over one million deaths annually, particularly in children under five years. This study was the first to examine plasma cytokines, chemokines and cellular immune responses in pre-school Nigerian children infected with Plasmodium falciparum from four semi-urban villages near Ile-Ife, Osun State, Nigeria.MethodsBlood was obtained from 231 children (aged 39–73 months) who were classified according to mean P. falciparum density per μl of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 34 publications
(47 reference statements)
3
23
1
Order By: Relevance
“…Signs of defective immune priming were also seen in this study, as shown by a decrease in the population of professional antigen presenting cells, dendritic cells, after exposure to P. falciparum while the number of these antigen presenting cells was similar to control cultures after exposure to P. vivax . In addition, the opposite effects of P. falciparum and P. vivax on the expression of HLA-DR in monocytes and dendritic cells described here supports previous findings reported by others [33]. Interestingly, the two types of antigen from P. falciparum increased expression of HLA-DR on the surface of monocytes which could be an incidence of severe outcome from immune over activation as reported in autoimmune disease patients [34].…”
Section: Discussionsupporting
confidence: 91%
“…Signs of defective immune priming were also seen in this study, as shown by a decrease in the population of professional antigen presenting cells, dendritic cells, after exposure to P. falciparum while the number of these antigen presenting cells was similar to control cultures after exposure to P. vivax . In addition, the opposite effects of P. falciparum and P. vivax on the expression of HLA-DR in monocytes and dendritic cells described here supports previous findings reported by others [33]. Interestingly, the two types of antigen from P. falciparum increased expression of HLA-DR on the surface of monocytes which could be an incidence of severe outcome from immune over activation as reported in autoimmune disease patients [34].…”
Section: Discussionsupporting
confidence: 91%
“…Analysis of THP-1 cells treated with lysates of red blood cells infected or not with Plasmodium falciparum revealed that NF90 influenced the levels of immune response proteins in response to malaria antigens on different levels: transcription, mRNA turnover, and translation. In line with previous results [24], the number of CD14 + cells declined after treatment with lysates of red blood cells infected with P. falciparum, while NF90 silencing restored CD14 + cells. We propose that NF90 regulates gene expression programs in THP-1 cells and influences the ability of these cells to respond to malaria antigens.…”
Section: Introductionsupporting
confidence: 92%
“…These molecular changes were translated into changes in cellular responses. The reduction of CD14 + THP-1 cells treated with iRBC lysates, compared with uRBC lysates, mimicked the decline in circulating CD14 + monocytes observed previously in individuals infected with P. falciparum [24,35], as monocytes differentiate into macrophages and dendritic cells to respond to the infection. In this scenario, NF90 appears to contribute to reducing CD14 + cells, since silencing NF90 elevated the CD14 + pool.…”
Section: Discussionsupporting
confidence: 75%
“…However, studies that have assessed this question have yielded conflicting results indicating that larger and better designed studies are needed. [17][18][19][20] To date, studies assessing the coinfection of helminths and malaria have mainly focused on the asexual forms of P. falciparum (reviewed in reference 21). However, there are indications that helminth infections may also influence the prevalence or density of P. falciparum gametocytes, the parasite stage responsible for transmission of infections to mosquitoes.…”
Section: Introductionmentioning
confidence: 99%